Peran PBB Melalui Universal Periodic Review dalam Meningkatkan Promosi Penegakan HAM di Indonesia tahun 2008-2012 - Astuti, Anak Agung Yessi Puji; Sushanti, Sukma; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2017), 2017)
ABSTRA CT Human Rights enforcement is emerging as a spotlight in the international arena. To support this effort, United Nations as one of the International Organization bodies that concern about human rights created a mechanism that called Universal Periodic Review (UPR). As one of the UN member states Indonesia also joined the UPR mechanism. This research will see the role of the UN through UPR in increasing the human rights enforcement in Indonesia. The timeframe of this research is from the Indonesia’s first cycle UPR in 2008 until 2012. Research method that used in this research is qualitative-descriptive and using several concepts such as the concept of Human Rights in International Relations and Role of International Organizations. After analyzing, it was found that UN can encourage Indonesia to join UPR mechanism because UN showed its independence as well as the influence of the power of International Organization that owned by UN. After Indonesia joined UPR, UN play its role to increasing the promotion of human rights enforcement in Indonesia through the UPR mechanism. Keywords : Human Rights, United Nations, Universal Periodic Review, Role of International Organizations, Indonesia